Student Teachers’ Study Profiles — Longitudinal Perspective to Research-Based Teacher Education - Lähteenmäki, Marko; Mikkilä-Erdmann, Mirjamaija; Laakkonen, Eero; Warinowski, Anu; Clinton, Janet (Professions and professionalism, 2024)
This study examined student teachers’ study profiles and achievement levels from selection through to the bachelor’s phase of their teacher education programmes. The latent profile analysis revealed two student teacher study profile subgroups associated with varying study achievement levels from the first three years of the teacher education programme. In a more detailed examination, the results revealed that the main differences occur during the bachelor’s phase of the teacher education programme, wherein student teachers are learning to understand the research-based teaching profession and how to conceptualise theories and more independently learn to write their bachelor’s theses. A gender comparison between subgroups revealed that male student teachers were more likely to be allocated to the less research-oriented subgroup and female students to the highly research-oriented subgroup. These findings are discussed with regard to how teacher education programmes could better support different learners.